2020
DOI: 10.1038/s41598-019-57070-x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and birth predictors of objectively measured physical activity and sedentary time in three population-based birth cohorts in Brazil

Abstract: physical inactivity is a global pandemic with no signs of improvement. prolonged sitting time is an emerging risk factor that exacerbates the health consequences of physical inactivity. Both behaviours are influenced by various individual and environmental factors but it remains unknown whether early-life exposures "program" these behaviours in later life. the current evidence is limited by a small number of studies which were primarily conducted in high-income countries, and a narrow range of early-life varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 43 publications
(45 reference statements)
1
10
0
Order By: Relevance
“…Associations were not explained by adjustment for other early life factors. These novel findings build on existing evidence demonstrating that early life factors influence physical activity behaviours in childhood, adolescence and early adulthood, [13][14][15][16] by showing associations remain in midlife.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Associations were not explained by adjustment for other early life factors. These novel findings build on existing evidence demonstrating that early life factors influence physical activity behaviours in childhood, adolescence and early adulthood, [13][14][15][16] by showing associations remain in midlife.…”
Section: Discussionsupporting
confidence: 78%
“…We identified a weak linear association between high birth weight and low MVPA, which has been previously reported in meta-analyses and cross-cohort studies 14 15 alongside inverse U-shaped 13 16 and null associations. 17 Ding et al 14 reported no association between gestational age and MVPA at ages 6, 18 or 30, whereas Tikanmäki et al 15 reported that those born preterm or post-term had lower levels of leisure-time physical activity at age 16 than regular term births. Here, we present the novel finding that post-term boys have lower levels of physical activity in midlife, with no association in girls.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
See 3 more Smart Citations